PLANT NATRIURETIC PEPTIDE A and Its Putative Receptor PNP-R2 Antagonize Salicylic Acid–Mediated Signaling and Cell Death. Issue 7 (14th May 2020) - Lee, Keun Pyo; Liu, Kaiwei; Kim, Eun Yu; Medina-Puche, Laura; Dong, Haihong; Duan, Jianli; Li, Mengping; Dogra, Vivek; Li, Yingrui; Lv, Ruiqing; Li, Zihao; Lozano-Duran, Rosa; et al.
Abstract : Intercellular signaling mediated by PNP-A and its putative receptor protein PNP-R2 counteracts SA-mediated plant stress responses. Abstract: The plant stress hormone salicylic acid (SA) participates in local and systemic acquired resistance, which eventually leads to whole-plant resistance to bacterial pathogens. However, if SA-mediated signaling is not appropriately controlled, plants incur defense-associated fitness costs such as growth inhibition and cell death. Despite its importance, to date only a few components counteracting the SA-primed stress responses have been identified in Arabidopsis ( Arabidopsis thaliana ). These include other plant hormones such as jasmonic acid and abscisic acid, and proteins such as LESION SIMULATING DISEASE1, a transcription coregulator. Here, we describe PLANT NATRIURETIC PEPTIDE A (PNP-A), a functional analog to vertebrate atrial natriuretic peptides, that appears to antagonize the SA-mediated plant stress responses. While loss of PNP-A potentiates SA-mediated signaling, exogenous application of synthetic PNP-A or overexpression of PNP-A significantly compromises the SA-primed immune responses. Moreover, we identify a plasma membrane–localized receptor-like protein, PNP-R2, that interacts with PNP-A and is required to initiate the PNP-A–mediated intracellular signaling. In summary, our work identifies a peptide and its putative cognate receptor as counteracting both SA-mediated signaling and SA-primed cell death in Arabidopsis.